The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s0100-46702005000400008
|View full text |Cite
|
Sign up to set email alerts
|

Determinação de cádmio em amostras de urina e soro humano por espectrometria de absorção atômica em forno de grafite usando irídio como modificador permanente

Abstract: Resumo:No presente estudo, foram investigadas diferentes substâncias para atuarem como modificadores químicos na determinação direta de cádmio em soro e urina humanos sem digestão prévia das amostras. A preparação da amostra foi feita diretamente nos copos do amostrador automático por diluição 1+4 de soro e 1+1 de urina com ácido nítrico 1% v/v contendo 0.02% v/v de cloreto de tricetil metil amônio (CTAC). Foram investigadas as melhores condições de determinação por meio de curvas de temperatura de pirólise e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Intra-and inter-assay precision was below the recommended values found in other studies for both analytes. [22][23][24]30 In this study we successfully demonstrated that there was no need for lengthy digestion prior to the analysis, which is subject to losses and contamination. Finally, the use of a permanent modier ensures the destruction of the matrix in situ providing the use of aqueous calibration, i.e.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Intra-and inter-assay precision was below the recommended values found in other studies for both analytes. [22][23][24]30 In this study we successfully demonstrated that there was no need for lengthy digestion prior to the analysis, which is subject to losses and contamination. Finally, the use of a permanent modier ensures the destruction of the matrix in situ providing the use of aqueous calibration, i.e.…”
Section: Discussionmentioning
confidence: 90%
“…The condition without the use of a modier was also studied. The lifetime of the graphite tube using a permanent modier without a decrease in sensitivity is more than 1000 cycles, 24,25 but was not investigated in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The condition without modifier was also studied. The lifetime of the graphite tube using a permanent modifier without a decrease in sensitivity is more than 1000 cycles (11,(12)(13)(14); however, this was not investigated in this study.…”
Section: Experimental Instrumentationmentioning
confidence: 99%